Lost angels [videorecording (DVD)] - Napper, Thomas Q.; Keener, Catherine (Cinema Libre Studio, 2013)
Looks at the plight of eight homeless persons living in the Skid Row section of downtown Los Angeles. Examines the effects of gentrification, mental illness and drug abuse, and the criminalization of homelessness on the individuals profiled.